Muscle invasive bladder cancer presenting as recurrent autonomic dysreflexia – a wolf in wolf's clothing. (3rd July 2020) - Fitzpatrick, Ryan; Baverstock, Richard
Abstract : Context: Autonomic dysreflexia is a potentially lethal condition experienced by spinal cord injury (SCI) patients. It has a wide range of causes, most of which are genitourinary in nature. However, there has been no documented case of primary bladder cancer as a trigger for recurrent autonomic dysreflexia. Findings: We present a case of a 51-year-old spinal cord injury patient with multiple presentations of autonomic dysreflexia. Work up revealed locally invasive bladder cancer, and following definitive surgery, his symptoms were alleviated. Conclusions: In SCI patients with recurrent AD, comprehensive work up with involvement of a specialized Urologist is required as AD may be the only presenting symptom of a serious underlying medical condition.